A Comparative Study Between the Stryker EZout Powered Acetabular Revision System and the Zimmer Explant Acetabular Cup Removal Systems. Issue 2 (June 2021) - Kwong, Louis; Billi, Fabrizio; Keller, Scott; Kavanaugh, Aaron; Luu, Andrew; Paprosky, Wayne
Abstract : The conservation of bone stock and the decrease of intraoperative acetabular fracture risk associated with revision surgery is a primary goal to improve the outcome of the procedure. The objective of this study was to evaluate and compare the performance of the Explant Acetabular Cup Removal System and the EZ out Powered Acetabular Revision System in an in vitro model. Acetabular components were implanted into instrumented composite hemipelvises and divided into 2 groups, EZ out System and Explant System. One experienced orthopedic surgeon and 1 orthopedic resident physician performed the removal procedures. The strains at various points in the periacetabular bone, the temperature at the implant-bone interface, the total time to removal, the torque applied to the implant and the amount of acetabular foam on each cup after extraction, as a surrogate for cavitary acetabular bone stock loss, were calculated for each test. Statistical analysis was conducted using 2-way multivariate analysis of variance followed by Tukey honestly significant difference multiple comparisons. The EZ out System required an overall lower force and torque ( P <0.0001, both) during removal, producing lower strains in the surrounding composite bone. The procedure was faster ( P <0.0001) and less energy demanding with the EZ out compared with the Explant. The amount of foam on the cup was on average less for the EZ out than for the Explant ( P <0.05). We found that the EZ out System is effective in achieving safe removal of a well-fixed acetabular component in an in vitro model of cementless fixation. This system should be considered as a reasonable alternative to manual removal techniques.